Advertising : - Mono (RotoVision, 2001)
Design for advertising is huge. This book takes a look at leading advertising campaigns from around the world and the design that has made them so successful. From print to screen-based, projects are diverse in terms of both scale and budget. The author devotes a chapter to each project with comments from designers, clients, repro houses and printers. Approximately 10 projects are featured, showing the process of design from original brief to finished product.